2023
DOI: 10.3390/buildings13061464
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Large-Scale Physical Model of Geosynthetic-Reinforced Piled Embankment and Analytical Design Methods

Abstract: The piled embankment represents one of the solutions for the realization of a soil body on a compressible subsoil where extended settlement or insufficient stability threatens the serviceability of related structures. Widely adopted analytical design procedures were analyzed: Marston’s formula and Hewlett and Randolph method contained in the British standard BS 8006-1, the German regulation EBGEO and the Dutch regulation CUR 226. Using these recommendations, the theoretical values of the individual parts of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…For example, one study [2] showed that the analytic design of geosynthetic-reinforced soil walls using the North American standard was extremely conservative, underestimating the geosynthetic performance by 50%. A more recent comparison [3] of analytical methods provided by technical standards also showed considerable overestimation of the loads acting on the reinforcement.…”
Section: Introductionmentioning
confidence: 96%
“…For example, one study [2] showed that the analytic design of geosynthetic-reinforced soil walls using the North American standard was extremely conservative, underestimating the geosynthetic performance by 50%. A more recent comparison [3] of analytical methods provided by technical standards also showed considerable overestimation of the loads acting on the reinforcement.…”
Section: Introductionmentioning
confidence: 96%
“…The soil arching phenomenon in a pile-supported granular embankment was demonstrated based on the two-dimensional finite element modeling approach [20]. The large-scale physical model was also utilized to simulate the behavior of the piled embankment reinforced with the basal geosynthetic reinforcement [21]. However, in the literature review, most studies focus on the load transfer mechanism for coarse materials or cohesionless soils, and the effects of cohesion of embankment soils were not considered in pile-supported embankments [22,23].…”
Section: Introductionmentioning
confidence: 99%